KEMAMPUAN PEDAGOGIK GURU DALAM MENGEMBANGKAN MATERI PENDIDIKAN AGAMA ISLAM SEKOLAH DASAR - Dewi Gita; Andi Anirah; Elya Elya; Andi Ardiansyah (AT TA'LIM : Jurnal Madrasah Ibtidaiyah, 2025)
The skill of educators in SD Inpres Donggala Kodi to create resources for Islamic Education in the 4th grade is essential for improving pupils' knowledge and regard for Islamic principles. The goal of this research is to analyze the educator's capability to create materials for Islamic Education in the 4th grade at SD Inpres Donggala Kodi, with a specific concentration on the subject of "Being a Virtuous Child," instead of encompassing the complete Islamic Education program. A qualitative research strategy is applied in this research, utilizing approaches to data collection, for example interviews, observations, and assessing documents. The findings demonstrate that the Islamic Education educator in the 4th grade at SD Inpres Donggala Kodi does have the ability to develop resources for Islamic Education. This skill is recognized as pedagogical competence, which is reinforced by the author's analysis that the educator is able to design appealing instructional resources by utilizing various materials (books, music videos, the Qur'an, hadith, and online applications) and applies different instructional strategies. Also, utilizing technology-based learning platforms can enhance student attention and incentive in discovering Islamic values. The meaning of this study emphasize the importance of improving educators' skills to create successful Islamic education resources to accomplish more extensive understanding and to grow a solid Islamic identity in pupils' lives.